Analysis of Accountability and Transparency of Village Fund Allocation in Katoi Village, North Kolaka Regency - Nadila, Nadila; Haliah, Haliah; Nirwana, Nirwana (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to evaluate the accountability and transparency levels in the Village Fund Allocation (ADD) administration at Katoi Village, North Kolaka Regency. The primary focus is on how the village administration administers the funds in compliance with the accountability and transparency guidelines outlined in the Minister of Home Affairs of the Republic of Indonesia's Regulation Number 113 of 2014. This study uses a qualitative method with a descriptive approach. Data were collected through interviews with related parties and documentation studies of village fund management reports. The study's findings show that Katoi Village's village fund management has been transparent and accountable, in compliance with the laws that are in place. However, there are still certain challenges with public information dissemination and the creation of more thorough financial reports.